Perception of the Russo-Ukrainian war and the images of Russia and Ukraine in the protest movement ‘Frankfurter Freigeister’ in Frankfurt (Oder) - Belozerova, Aleksandra (Language and Public Sphere, 2024)
The German government's reaction to Russia's invasion of Ukraine on 24 February 2022, and in particular the policy of sanctions against Russia and the supply of arms to Ukraine, led to a wave of discontent in parts of German society. The issue of the Russo-Ukrainian war was taken up by protest movements in various cities that had already formed at that time (including during the COVID-19 pandemic). The most regular and numerous were the demonstrations in East Germany, where thousands of people protested every Monday in the so-called ‘Montagsdemonstration’. The ‘Frankfurter Freigeister’, a protest movement in Frankfurt on the Oder in Brandenburg, were no exception. The multitude of Russian flags, the contradictory demands and the aggressive actions of the protesters raise a number of questions about their perception of the Russo-Ukrainian war itself and of Russia and Ukraine in general. This article looks at the issues raised by the ‘Frankfurter Freigeister’ in relation to the war and the factors that may be driving them. But first of all, how does this protest movement perceive the Russo-Ukrainian war and the role of Russia and Ukraine in it?